Fasting ghrelin but not PYY(3-36) is associated with insulin-resistance independently of body weight in Wistar rats - Antunes,Luciana da Conceição (2014)
Objective: The objective of this study was to evaluate the association between insulin-resistance and fasting levels of ghrelin and PYY in Wistar rats. Materials and methods: A total of 25 male Wistar rats, weighing 200-300 g, was included in this study. The animals were maintained in cages with a 12/12h light-dark cycle and fed standard chow and water ad libitum. After 12-h overnight fasting, ghrelin, PYY, insulin and glucose values were determined. Insulin resistance was assessed by means of the HOMA-IR, which was ranked and the median was used as a cut-off value to categorize insulin-resistance. HOMA-IR values equal and above 2.62 were considered insulin-resistant (IR) while values below 2.62 were considered insulin sensitive (IS). Differences between means were determined using the Student t-test. Multiple regression and Pearson’s correlation test were used to evaluate the association between variables. Results: HOMA-IR median IQ range values for IS and IR groups were, respectively, 1.56 (0.89 – 2.16) vs. [4.06 (3.50 – 4.61); p < 0.001]. The IR group presented increased levels of fasting ghrelin, PYY and insulin respectively: [50.35 (25.99 – 74.71) pg/mL vs. 12.33 (8.77 – 15.89) pg/mL; p = 0.001]; [54.38 (37.50 – 71.26) pg/mL vs. 33.17 (22.34 – 43.99) pg/mL; p = 0.016]; [18.04 (14.48 – 21.60) uU/mL vs. 7.09 (4.83 – 9.35) uU/mL; p = 0.001]. Ghrelin, but not PYY, correlated linearly and positively with HOMA-IR: ghrelin vs. HOMA-IR (r = 0.52; p = 0.008), and PYY vs. HOMA-IR (r = 0.22; p = 0.200). This correlation was independent of body weight. Conclusion: Fasting ghrelin and PYY serum levels are increased in lean, relatively insulin resistant Wistar rats, and this increase is independent of weight.